CBT Variations in Treatment of Positive Symptoms for People with Schizophrenia: Scoping Review - Primasari, Herdini; Kusrohmaniah, Sri (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2025)
Schizophrenia is a disorder that affects thoughts, feelings, and behavior, often accompanied by positive symptoms such as delusions and hallucinations. CBT (cognitive behavioral therapy) is a psychotherapeutic approach that help individuals with schizophrenia develop coping strategies and reduce positive symptoms. This scoping review research maps the variations of CBT types through 24 journals from PubMed, Google Scholar, and ScienceDirect (published from 2000 to 2022), which studied participants aged 18–65 years without comorbidities. CBT can be applied individually or in groups, including general cognitive behavioral therapy, acceptance-based, cognitive behavioral social skill training, brief CBT for psychosis (culturally adapted), guided self-help, and module-based for specific symptoms. Most participants in the reviewed study were of age 30 to 50, with the majority being male. Based on the scoping review conducted, CBT can be conducted with therapist guidance or self-administered. CBT was also found to be effective in addressing positive symptoms in individuals with schizophrenia.